2005
DOI: 10.1107/s1600536805012900
|View full text |Cite
|
Sign up to set email alerts
|

(E,E)-α-(Methoxyimino)-2-[({1-[3-(trifluoromethyl)phenyl]ethylidene}amino)oxymethyl]benzeneacetic acid

Abstract: The crystal structure of the title compound, C19H17F3N2O4, a metabolite of the fungicide trifloxy­strobin (TFS), contains one mol­ecule in the asymmetric unit. The CF3 group is disordered over two positions. The important characteristics of the mol­ecule are the two C=N bonds in an E,E configuration, one in the β‐methoxy system and the other in the oxy­methyl side chain between the two aromatic rings. The mol­ecules are linked via an O—H⋯N hydrogen bond and an infinite spiral is formed along the b‐axis directi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Isomerization was of minor importance due to the absence of light. The same studies demonstrated that adsorption of both the parent compound and its metabolite acids follow linear and Freundlich isotherms; the extent of adsorption depends upon the binding sites available in organic matter and clay (2,3).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Isomerization was of minor importance due to the absence of light. The same studies demonstrated that adsorption of both the parent compound and its metabolite acids follow linear and Freundlich isotherms; the extent of adsorption depends upon the binding sites available in organic matter and clay (2,3).…”
Section: Introductionmentioning
confidence: 87%
“…Trifloxystrobin degrades rapidly in water and soil by mechanisms including metabolism, photolysis, and hydrolysis. Banerjee et al , showed that soil hydrolysis was the dominant pathway of degradation of trifloxystrobin and that the major metabolite was the E , E acid. Isomerization was of minor importance due to the absence of light.…”
Section: Introductionmentioning
confidence: 99%
“…Evaporation gave 4.48 g of a clear liquid, which was further purified by recrystallization from hexane/acetone (95:5) to obtain 3.52 g of the acid derivative as white crystals (72.9%). The preparation of this acid derivative has been described in the literature , but no physical or spectroscopic data have been previously given for it. A detailed description of these data follows: mp 102−103 °C (from slow evaporation of a CHCl 3 /hexane solution); 1 H NMR (DMSO- d 6 ), δ13.29 (1H, br s, COOH), 7.91 (1H, br d J = 7.5 Hz, H-6 PhCF 3 ), 7.90 (1H, br s, H-2 PhCF 3 ), 7.73 (1H, br d, J = 7.5 Hz, H-4 PhCF 3 ), 7.63 (1H, br t, J = 7.5 Hz, H-5 PhCF 3 ), 7.47 (1H, br dd, J = 7, 2 Hz, H-6 Ph), 7.42 (1H, ddd, J = 7, 7, 1.5 Hz, H-5 Ph), 7.37 (1H, ddd, J = 7, 7, 2 Hz, H-4 Ph), 7.18 (1H, dd, J = 7, 1.5 Hz, H-3 Ph), 5.07 (2H, s, CH 2 O), 3.89 (3H, s, OCH 3 ), 2.20 (3H, s, CH 3 ); 13 C NMR (DMSO- d 6 ), δ 163.73 (CO), 153.59 (CN), 149.87 (C-2), 136.77 (C-1 PhCF 3 ), 135.39 (C-2 Ph), 130.76 (C-1 Ph), 129.89 (C-6 PhCF 3 ), 129.63 (C-5 PhCF 3 ), 129.21 (q, J = 32 Hz, C-3 PhCF 3 ), 128.76 (C-6 Ph), 128.55 and 128.52 (C-3 Ph and C-5 Ph), 127.61 (C-4 Ph), 125.70 (q, J = 3.5 Hz, C-4 PhCF 3 ), 123.98 (q, J = 272 Hz, CF 3 ), 122.12 (q, J = 3.5 Hz, C-2 PhCF 3 ), 74.38 (CH 2 O), 62.92 (CH 3 O), 12.22 (CH 3 ); IR (KBr), 3420, 3066, 2941, 2880, 1705, 1340, 1294, 1281, 1118, 1072, 1046, 1005, 728, 697 cm −1 ; MS (EI), m / z 363 (M + − OCH 3 , 0.5), 319 (1), 317 (7), 301 (4), 192 (3), 172 (3), 151 (2), 117 (11), 116 (100); HRMS, calcd for C 18 H 14 F 3 N 2 O 3 (M + − OCH 3 ) 363.09565, found 363.09614; UV (100 mM sodium phosphate buffer, pH 7.4), ϵ (280 nm) = 2.69 mM −1 cm −1 , ϵ (260 nm) = 10.20 mM −1 cm −1 .…”
Section: Methodsmentioning
confidence: 99%
“…Evaporation gave 4.09 g of a white solid (85.6%), which was used in the next steps without further purification. The preparation of this acid derivative has been described in the literature (15,16), but no physical or spectroscopic data have been previously given for it. A detailed description of these data follows: mp 139-140 °C (from slow evaporation of a CHCl3/hexane solution); (15), 116 (100), 89 (11); HRMS, calcd for C 17H17NO4 299.11576, found 299.11652; UV (100 mM sodium phosphate buffer, pH 7.4), (280 nm) ) 1.37 mM -1 cm -1 , (260 nm) ) 2.86 mM -1 cm -1 .…”
Section: E)-2-(methoxyimino)-2-(2-(o-tolyloxymethyl)phenyl)acetic Aci...mentioning
confidence: 99%